The Use of AID to Manage International Migration: The Case of Ghana - Quartey, P.; Arthur, P. (Ghana journal of Development Studies, 2008)
The benefits as well as the cost of international migration have been debated considerably in recent times. Although the debate on whether the benefits outweigh the cost or vice versa remains a puzzle, it is quite evident that a well-managed international migration will bring net positive benefits to both the sending and receiving countries. The issue that rises is how migration is managed. An important alternative that has received little discussion but is being proposed at the policy level is to use aid to reward countries with better migration policies. Whether this option is a feasible and efficient alternative is the focus of this paper. The paper draws from various case studies on attempts to use aid to manage international migration for analysis. It is argues in the paper that the success of using aid to manage international migration from developing countries like Ghana critically depends on the size of the funds invested in the home country and the significance of its impact on livelihood in the sending countries. Secondly, it will depend critically on how the funds are able to empower people to increase their earning capacity at home. Moreover, it also depends to a large extent on the political climate within the sending countries. The paper concludes that it is essential to adopt a holistic approach that involves all stakeholders in the implementation of international migration management Policy.
Keywords: International Migration; Aid Flows; Aid Management Policies; Migration Patterns; Skilled Labor